EVALUATION MANAGEMENT MODEL IN LEARNING - Titin Suhartini Kaaba; Yinarti Hida (Tadbir: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to see the evaluation management model in learning. The method used in this research is literature because the data obtained comes from books. The results of the study found that learning evaluation is important because it becomes a benchmark for the success of a process. In addition, evaluation also serves to provide a recommendation so that each learning process carried out can be of high quality and quality